Recent Advances in Visible-Light-Promoted Copper Catalysis in Organic Reactions - Xiong, Yang; Li, Sijia; Xiao, Haijing; Zhang, Guozhu (Synthesis, 2021)
In recent years, visible-light-mediated copper photocatalysis has emerged as an attractive strategy for the diverse construction of basic bonds in an ecologically benign and cost-effective fashion. The intense activity in these areas has been stimulated by the distinctive properties of copper photocatalysts and has led to the rapid development and expansion of their applications. In this review, we focus on a series of significant achievements in the use of copper complexes as standalone photocatalysts in organic reactions to exhibit their high flexibility and potential in synthetic chemistry.1 Introduction2 Redox Coupling Reactions2.1 Carbon–Nitrogen Redox Coupling Reactions2.2 Carbon–Carbon Redox Coupling Reactions3 Oxidative Coupling Reactions4 Difunctionalization of Olefins5 C–H Bond Functionalization6 Radical Alkylation of Imines7 Conclusions and Outlook
Keywords: visible-light-mediated; copper photocatalysis; cross-coupling; asymmetric; functionalization